Potential involvement of KANK1 haploinsufficiency in centrosome aberrations - Imamura, Ikumi; Kiyama, Ryoiti (Biochimica et biophysica acta. General subjects, 2024)
KANK1 was found as a tumor suppressor gene based on frequent deletions in renal cell carcinoma and the inhibitory activity of tumor cell proliferation. Previously, we reported that knockdown of KANK1 induced centrosomal amplification, leading to abnormal cell division, through the hyperactivation of RhoA small GTPase. Here, we investigated the loss of KANK1 function by performing CRISPR/Cas9-based genome editing to knockout the gene. After several rounds of genome editing, however, there were no cell lines with complete loss of KANK1, and the less the wild-type KANK1 dosage, the greater the number of cells with abnormal numbers of centrosomes and rates of cell-doubling and apoptosis, suggesting the involvement of KANK1 haploinsufficiency in centrosome aberrations. The rescue of KANK1-knockdown cells with a KANK1-expressing plasmid restored the rates of cells exhibiting centrosomal amplification to the control level. RNA-sequencing analysis of the cells with reduced dosages of functional KANK1 revealed potential involvement of other cell proliferation-related genes, such as EGR1, MDGA2, and BMP3, which have been reported to show haploinsufficiency when they function. When EGR1 protein expression was reduced by siRNA technology, the number of cells exhibiting centrosomal amplification increased, along with the reduction of KANK1 protein expression, suggesting their functional relationship. Thus, KANK1 haploinsufficiency may contribute to centrosome aberrations through the network of haploinsufficiency-related genes. •CRISPR/Cas9-based genome editing was applied to knockout the KANK1 gene.•The dosage of KANK1 expression was examined to evaluate its effect on centrosomal functions.•KANK1 partial knockout resulted in anomaly of centrosome numbers, cell-doubling times and apoptosis.•Involvement of KANK1 haploinsufficiency in centrosome aberrations was suggested.•Potential contribution of KANK1 haploinsufficiency to centrosome aberrations through gene networks is discussed.